2011
DOI: 10.1002/dc.21746
|View full text |Cite
|
Sign up to set email alerts
|

Slug regulates E‐cadherin expression in metastatic adenocarcinoma cells isolated from pleural fluid

Abstract: Slug protein is a key regulator of epithelial-mesenchymal transition, but its expression in cancer is less well studied. To evaluate the expression of slug, E-cadherin and vimentin in adenocarcinoma cells from malignant pleural effusions, we analyzed 121 malignant pleural fluid specimens. Twenty-eight nonmalignant pleural fluid specimens were analyzed as control. Besides clinical cytological diagnosis tests, immunofluorescence, immunocytochemistry and Western blotting methods were used. Results showed strong m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…EMT is one of the effective pathways of tumor cell migration and the most important step of tumor cell invasion and metastasis [ 17 ]. The most important feature is that the expression of E-cadherin in epithelial type is decreased, while the expression of N-cadherin and vimentin in interstitial type is increased [ 18 ]. This is called the "cadherin transition".…”
Section: Discussionmentioning
confidence: 99%
“…EMT is one of the effective pathways of tumor cell migration and the most important step of tumor cell invasion and metastasis [ 17 ]. The most important feature is that the expression of E-cadherin in epithelial type is decreased, while the expression of N-cadherin and vimentin in interstitial type is increased [ 18 ]. This is called the "cadherin transition".…”
Section: Discussionmentioning
confidence: 99%
“…13 Numerous studies have shown that E-cadherin may represent a potentially valuable marker of malignant effusion. 14–17 E-Cadherin was found to be highly expressed in pleural effusions from patients with primary lung adenocarcinoma, small cell lung cancer, breast cancer and ovarian cancer. 17–19 However, these findings remain controversial.…”
Section: Introductionmentioning
confidence: 99%